Influence of Triple-Negative versus Luminal A Breast Cancer Subtype on Choice of Autologous versus Implant-Based Delayed-Immediate Breast Reconstruction - Dickey, Ryan M.; Amaya, Joshua; Teotia, Sumeet S.; Haddock, Nicholas T. (Journal of Reconstructive Microsurgery, 2021)
Background Triple-negative (TN) and luminal A breast cancer molecular subtypes have divergent clinical and prognostic characteristics for breast cancer patients. Our study aims to compare the reconstructive choice of these two groups from the time they receive a tissue expander (TE) to the time they complete autologous or implant-based breast reconstruction.Methods A total of 255 patients who underwent delayed-immediate breast reconstruction with TE placement from 2013 to 2017 diagnosed with either TN (n = 73) or luminal A (n = 182) invasive breast cancer subtype seen by two surgeons at a single institution were identified. Preference of autologous and implant-based reconstruction was analyzed, along with TE complications, race, age, body mass index (BMI), smoking, adjuvant therapy, and comorbidities.Results There was a significant difference in the choice of implant- or autologous-based reconstruction among these two groups (p < 0.05). A greater proportion of luminal A patients underwent implant-based reconstruction (63.47%) and a greater proportion of TN patients underwent autologous-based reconstruction (53.13%). With regard to TE outcomes, there was no significant difference between the two groups with regard to duration of TE placement by reconstructive type or TE surgical complications. Significantly, more TN patients underwent radiation therapy (p < 0.01) and neoadjuvant chemotherapy (p < 0.0001) than luminal A patients. BMI, comorbidities, radiation therapy, and overall TE complications were identified as predictive factors of patients electing for autologous reconstruction over implants.Conclusion TN breast cancer patients mostly chose autologous-based reconstruction, while luminal A patients chose implant-based reconstruction. Both patient groups carried their TEs for similar duration with similar complication profile. Radiation therapy is likely a major factor in the decision for the type of delayed-immediate reconstruction among this population.
Keywords: breast reconstruction; luminal A; triple negative